Disseminated nocardiosis in a patient with AIDS and B-cell non-Hodgkin’s lymphoma: a case report - Delvis R. Reverón; David M. Flora-Noda; Lily M. Soto; Maribel Dolande; Juan Frey; Aleiram Chaurio; Bárbara D. Ruiz-Alayón; Jocays Caldera; Fhabián S. Carrión-Nessi; David A. Forero-Peña (BMC Infectious Diseases)
Abstract Background Disseminated nocardiosis is a rare and potentially fatal disease, with a higher incidence in immunocompromised patients, such as those living with human immunodeficiency virus (HIV) or hematological malignancies, including lymphoma. Information on Nocardia spp. infection in Venezuela is limited. Case presentation We present the case of a 62-year-old male patient, recently diagnosed with HIV, who exhibited prolonged fever and unintentional weight loss. Paraclinical tests revealed pancytopenia and a marked elevation of lactate dehydrogenase. Disseminated histoplasmosis was suspected, prompting a bone marrow (BM) aspirate. Culture and molecular studies for Histoplasma spp. and Mycobacterium tuberculosis in BM samples were negative. Antiretroviral therapy with tenofovir/lamivudine/dolutegravir was initiated, but the patient subsequently experienced clinical deterioration, including ascites, pericardial effusion, and respiratory failure. Post-mortem biopsy and immunohistochemistry identified non-Hodgkin’s lymphoma of B-cell lineage, and mycological culture of BM isolated Nocardia farcinica. Conclusion Disseminated nocardiosis may mimic histoplasmosis. Nocardia spp. infection should be considered in HIV patients, particularly in advanced stages of infection.